Interfacial activation-based molecular bioimprinting of lipolytic enzymes. - Mingarro, I (1995)
Interfacial activation-based molecular (bio)-imprinting (IAMI) has been developed to rationally improve the performance of lipolytic enzymes in nonaqueous environments. The strategy combinedly exploits (i) the known dramatic enhancement of the protein conformational rigidity in a water-restricted milieu and (ii) the reported conformational changes associated with the activation of these enzymes at lipid-water interfaces, which basically involves an increased substrate accessibility to the active site and/or an induction of a more competent catalytic machinery. Six model enzymes have been assayed in several model reactions in nonaqueous media. The results, rationalized in light of the present biochemical and structural knowledge, show that the IAMI approach represents a straightforward, versatile method to generate manageable, activated (kinetically trapped) forms of lipolytic enzymes, providing under optimal conditions nonaqueous rate enhancements of up to two orders of magnitude. It is also shown that imprintability of lipolytic enzymes depends not only on the nature of the enzyme but also on the "quality" of the interface used as the template.